The Labor of Building Trust: Traditional and Engagement Discourses for Practicing Journalism in a Digital Age. (December 2021) - Zahay, Megan L.; Jensen, Kelly; Xia, Yiping; Robinson, Sue
This work of rhetorical analysis interrogates the understanding of journalism as a deliberative instrument in democracy. With 42 in-depth interviews and hundreds of pages of text from websites, social media, and trade press articles, we find a major shift occurring in the United States between more traditional reporters and a growing class often calling themselves "engagement specialists." These engagement-oriented journalists assert a responsibility to relationally engage with citizens in person and online, making space for them in the news production process. These emerging routines of trust-building are informing a new rhetoric around what it means to "do journalism."